Research on the regularity of data factor formation and value release - Zeyu WANG; Ailin LYU; Shu YAN (大数据, 2023)
Based on the conceptual and historical analysis of data and production factors, it was proposed that the data factor was the computer data and its derivative that was gathered, sorted and processed according to specific production needs and participated in social production and operation activities.It should focus on the value of data factor as a new driving force for economic growth and production development.It was summarized the three value release ways of data factor, namely, business operation by data, intelligent analysis by data and external effects by data exchange, and it should be given full attention in the process of promoting the development of data factor.